Application of Spinner Media in Improving Arabic Learning Outcomes of Madrasah Tsanawiyah Students - Sitti Mutmainnah Arham Arham; Agussalim Beddu Malla; Ratika Ningsih; Nurjannah (Program Studi Pendidikan Bahasa Arab, Fakultas Agama Islam, Universitas Muslim Indonesia, 2026)
This study aims to examine the effectiveness of spinner media in improving Arabic language learning outcomes of Grade VII A students at MTs Muallimin Muhammadiyah Makassar. A Classroom Action Research (CAR) design following the Kemmis and McTaggart model was employed across two cycles, each comprising four stages: planning, action, observation, and reflection. The research was motivated by low student achievement and limited motivation resulting from conventional, teacher-centered instruction. Results demonstrate consistent improvement across each phase. In the pre-cycle stage, only 22% of students met the minimum passing standard (KKM), with a class mean score of 57. Following spinner media implementation in Cycle I, the completeness rate rose to 48% with a mean of 74. In Cycle II, results surpassed the KKM of 75, reaching 85% completeness and a mean score of 85. Student activity scores improved from